Identification of culture-dependent microbes from mangroves reveals dominance of Bacillus including medically important species based on DNA signature - RANDE DECHAVEZ; MA. LYN CALUB; DONA ROSE GENOBATA; RAUL BALACUIT; REIZL JOSE; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dechavez R, Calub ML, Genobata DR, Balacuit R, Jose R, Tabugo SR. 2022. Identification of culture-dependent microbes from mangroves reveals dominance of Bacillus including medically important species based on DNA signature. Biodiversitas 23: 5342-5350. Mangroves are among the most crucial plant hosts in the marine environment because of their notable role in the ecosystem and their benefits. Identification of plant-associated and culture-dependent microbes is key to having a rich reservoir of bioactive substances. DNA barcoding was done based on 16S rRNA gene and ITS region. In this study, seven (7) mangrove species were identified as hosts. Results show that most bacterial isolates from plant leaves were gram-positive bacteria belonging to phylum: Firmicutes and genus Bacillus. Phylogenetic inference reveals a diverse non-monophyletic group with medically and economically necessary species. Among the host plants, Sonneratia alba harbored the most species of bacteria and fungi. These include two medically important strains of B. cereus and B. thuringiensis and host-specific bacteria like B. altitudinis in S. alba, B. velezensis in Rhizophora apiculata, B. clausii in Avicennia marina and B. firmus in A. marina were revealed. Meanwhile, some bacteria like B. subtilis and B. megaterium were found in three host species and B. cereus was the most abundant being recorded in four host plants. Diverse strains of fungi, Aspergillus sp., A. nomiae, A. tubingensis and A. niger were also present. This study served as baseline data for future research on diversity and host ecology for possible drug discovery.